(untitled) (Scientific journal of the Fergana State University, 2025)
In the article, the need to modernize the personnel training system was researched on a scientific basis, and the specific development trends of this system in the new Uzbekistan were analyzed. Also, the role of modernization of the personnel training system in the field of public service and civil service is studied in detail in the article. Also, on the basis of the scientific conclusions obtained in the article, the issues of applying international experience to practical life in the further improvement of the field of civil service in New Uzbekistan are widely discussed.